The Experiences of Disadvantages and Discrimination Among the Tea Garden Workers in Bangladesh: An Overview - Md Abdul Jalil; Mohammad Ali Oakkas (Asian Social Work Journal, 2018)
This paper aims to understand the experiences of disadvantages and discrimination among tea garden workers in Bangladesh. Based on the interviews of 75 tea garden workers, the paper identified few domains where they experience disadvantage and discrimination. The paper recommended government intervention and NGO and INGO initiatives to ensure educational opportunities for their children, provide healthcare facilities and increase wages for the garden workers. The paper has implications for the international community to ensure equitable society and social justice for the vulnerable and minority groups all over the world.